KERUKUNAN ANTAR UMAT BERAGAMA KRISTEN DAN ISLAM DI SOE, NUSA TENGGARA TIMUR - Yustiani Yustiani (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
Christian and Islamic communities at Taubueno village, city of Soe, each has various activities. Those activities are observant of religious duties, social religious activities and religious social community activi ties.In these two communities there is relationship in social religious and social community activities. In social religious activities, they cooperate in celebrating religious festal day and in constructing worship places. In social community activities, they are hand in hand doing environmental volunteer works, social works, and cooperation in organizing family ritual. Their cooperation is based on their own religious doctrines and same national cultures. However, there was ever a religious conflict among them.